Effects of merged holes, partial thread removal, and offset holes on fatigue strengths of titanium locking plates. (June 2022) - Muthusamy, Balraj; Chao, Ching-Kong; Su, Shinyen Jason; Cheng, Cheng-Wen; Lin, Jinn
Abstract: Background: This study investigated the effects of screw hole merging, thread removal, and screw hole offset on the mechanical properties of locking plates. Methods: Finite element models were used to develop the optimal design of the merged holes. Four titanium locking plates with different hole designs were analyzed. Type I had threaded round holes. Type II had merged holes. Type III had merged holes with partial thread removal. Type IV had threaded offset holes. Mechanical experiments similar to finite element analyses were conducted and compared. Screw bending tests were used to assess the screw holding power. Findings: Finite element analyses showed the optimal merging distance between two round screw holes was 3.5 mm with 2/3 circumferences in each hole. The stresses of types II and III were respectively 6.42% and 7.33%, lower than that of type I. The stress of type IV was 1.66% higher than that of type I. In the mechanical tests, the fatigue lives of types II and III were respectively 3.86 and 7.16 times higher than that of type I. The fatigue life of type IV was 37% lower than that of type I. The differences in the bending strengths of screws were insignificant. Interpretation: Merging holes could mitigate screw hole stress and increase the fatigue lives of the plates significantly. Partial thread removal could further improve the fatigue life. Merging holes and thread removal did not decrease the screw holding power significantly. The fatigue lives were significantly decreased in plates with offset holes. Highlights: Screw hole merging could markedly enhance fatigue lives of locking plates. Partial thread removal could significantly increase the fatigue lives of plates. Removing 1/3 of threads in merged hole does not affect the screw's holding power. Offset holes in locking plates can reduce fatigue lives significantly.